Delivering the Past: Providing Personalized Ancestral Tourism Experiences. (April 2017) - Alexander, Matthew; Bryce, Derek; Murdy, Samantha
Heritage tourism is increasingly viewed as both an individual and experiential phenomenon as well as being related to specific attributes of a destination. Ancestral tourism fits the former perspective and centers on tourists traveling to sites which they perceive to be a "homeland" where, during the visit, they attempt to discover more about their own heritage. This study explores ancestral tourism from a provider perspective focusing on the delivery of tourist experiences and relationships between tourists and the place visited. The research is based on a qualitative study of tourist and nontourist specific providers across Scotland with data collected using in-depth interviews. This study reveals a phenomenon that delivers deeply personal experiences to visitors and where encounters involve intense, often lengthy, interactions between visitors and providers. Ancestral tourism experiences are also often centered on tourism provision within local communities, which can present challenges to both provider and tourist alike.